Analysis of Fish Export Business in CV. Hadi Wijaya Abadi Tanjung Medang Village, Rupat Utara District, Riau Province - Gultom, Vid Gerald; Darwis, Darwis; Bathara, Lamun (Fakultas Perikanan dan Kelautan Universitas Riau, 2024)
International trade is vital for Indonesia because export activities, the country's main component, can drive the economy. CV Hadi Wijaya Abadi exports fresh fish to Kualalinggi (Melaka). The types of fish exported are Chirocentrus drab, Scomberomorus commerson, Sphyraena barracuda, Epinephelus sp, and Arius thalassinus. This study aims to analyze the amount of investment and profit in fish exports at CV Hadi Wijaya Abadi and the feasibility of business in capturing fisheries exports at CV Hadi Wijaya Abadi. The method used is the survey method. The number of respondents who were used as the object of this study, as many as 11 people, was considered sufficient to obtain export analysis research data. The types of data collected include primary data and secondary data. This data was obtained from direct interviews using questionnaires and literature. The study results are: 1) The total investment of export businesses amounted to IDR 2,971,820,000, obtained from fixed capital of IDR 2,845,580,000 and working capital of IDR.126,240,000. 2) Revenue Cost of Ratio (RCR) obtained a value of 1.22, Financial Rate of Return (FRR) of 61.35%, and in the Payback Period of Capital (PPC) analysis obtained a result of 5.8, which means it takes five years and ten months. The feasibility analysis of the export business at CV Hadi Wijaya Abadi is based on existing provisions/criteria, and it can be concluded that this business is profitable and feasible to run